The Influence of Cognitive Abilities on the Choice of Employment Sector in Indonesia - Najib, Nauval; Agustin, Devina; Fitria, Riska; Hartarto, Romi Bhakti (Jurnal Ekonomi Indonesia, 2024)
Cognitive ability plays a crucial role in determining the overall quality of human resources. However, the level of cognitive ability remains a significant concern in Indonesia, as the country ranks 10th in Asia. The primary objective of this study is to analyse the impact of cognitive ability levels on the choice of employment sector in Indonesia. The findings can potentially aid policymakers and stakeholders in devising targeted strategies to improve the country’s cognitive abilities and effectively allocate human resources across different sectors. The study utilises data from the fifth round of the Indonesian Family Life Survey (IFLS-5) in 2014 and the multinomial logit model for the analysis. The findings highlight a significant relationship between cognitive ability and the choice of employment sector. Individuals with higher cognitive skills are more inclined to opt for the formal sector as their preferred employment choice rather than agriculture and entrepreneurship. Policymakers should strengthen cognitive skills element in education and job training for Indonesian workers in order to distribute human resources across sectors better and stimulate economic growth.